2002
DOI: 10.1002/jmri.10054
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging of inflammatory bowel disease: Evaluation in a rabbit model

Abstract: Purpose: To correlate intestinal contrast enhancement and wall thickening with the degree of inflammation in an experimental model of inflammatory bowel disease. Materials and Methods:Inflammatory bowel disease was elicited in 39 New Zealand White rabbits by rectal instillation of 2,4,6-trinitrobenzene sulphonic acid (TNBA). Magnetic resonance imaging (MRI) was used to determine bowel wall thickness and intestinal contrast enhancement after the administration of 0.1 mmol/kg of gadodiamide intravenously. MR mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…Jejunum has a larger surface area compared to ileum due to the valvula conniventes and may be more resistant to the local effect of TNBS-EtOH. These findings are in accordance with a recent experimental study by Knollmann et al where they used TNBS-EtOH to induce inflammatory lesions in the large bowel of rabbits [6]. This study also reported that a bowel wall thickness below 3 mm could not exclude the presence of significant inflammation.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Jejunum has a larger surface area compared to ileum due to the valvula conniventes and may be more resistant to the local effect of TNBS-EtOH. These findings are in accordance with a recent experimental study by Knollmann et al where they used TNBS-EtOH to induce inflammatory lesions in the large bowel of rabbits [6]. This study also reported that a bowel wall thickness below 3 mm could not exclude the presence of significant inflammation.…”
Section: Discussionsupporting
confidence: 94%
“…The bowel wall was defined thickened if measured more than 3 mm. Pathological bowel wall enhancement was defined as visually increased intensity of the bowel wall compared to normal bowel wall after intravenous gadolinium and the finding was confirmed with ROI measurements [6]. Bowel stenosis was defined as more than 60% narrowing of bowel lumen compared to adjacent normal bowel [7][8][9].…”
Section: Mri Evaluationmentioning
confidence: 99%
“…The reason of this discrepancy could be explained first, by the thin bowel wall thickness in rabbits [14] and then pressure effect of the RF coil against the wall can prevent to visualize all the layers [15]. As demonstrated in our experiment, in vivo imaging with endoluminal approach provided high-quality images without significant blurring and motion artifacts despite high in-plane resolution and image acquisition times of several minutes.…”
Section: Discussioncontrasting
confidence: 48%
“…The variety of published literature does not suggest that models of colitis are inherently variable or short-lived, yet this is in fact the reality, as emphasized by Wirtz et al 4 and noted by Knollmann et al 16 Similar experiences have been made by other groups (verbal reports, personal communications), suggesting these problems are common phenomena. Variability resides in the response to the pro-colitic agent and the time course of the resulting pathology, which itself may be divided into 2 stages: First is the acute injury phase due to the actions of TNBS in combination with the mucosal barrierbreaker ethanol.…”
Section: Discussionmentioning
confidence: 60%
“…In humans, breath-holding, often in combination with peristalsis-suppressing drugs, allows the gut to be visualized in greater detail with far fewer motion artifacts. MRI has also been applied to colitis in mice 14,15 and rabbits, 16 but not rats. In animals anesthetized to reduce motion, respiration gating can also provide relatively motion-free images of the gut.…”
mentioning
confidence: 99%